(3LRA ef GdaJhMGJ GdecjIs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s ((3jhSa GdcGTjfjs)
(3ChdgG (B:s
(3ef aJhMGJ SjOj GdTjN GdCcHQ bOS Gddg SQg bGd SjOj GdTjN QVj Gddg Yfg aj GdaJhMGJ deG Ndb Gddg JYGdi GdehdOGJ ef GdLeGOGJ hGdfHGJ hGdMjhGfs
(3BNQgG (B:s
(3cdjeGJ QHj hdh LFfG HeKdg eOOG aGcJajfG Ydi eG CbefG hhbafG YfOeG hbafG hGddg jbhd GdMb hjgOj GdSHjds
(3Hg OhGFQ hQShe, hgh YHGQI Yf LRA UZjQ ef cJGH GdaJhMGJ GdecjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3cTa GdXfhf(B: 2 / 1238s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs